Analysis of Perception and Adaptation to Climate Change by Farmers in Gulmi District, Nepal - Ghimire, Narhari P; Aryal, Maniratna (Journal of Agriculture and Environment, 2013)
Climate change is a global challenge, highly affecting the developing countries with low adapting capacity, of which Nepal is not an exception. Climate change highly affects agriculture and livelihoods of farmers in Nepal. Its objectives are farmer's perceptions, witnesses and experiences on effects of climate change on agriculture and adaptations by farmers. Primary informations collected through structured questionnaire of household survey by selecting samples randomly. Information on primary and secondary data sources verified scientifically by trend analysis of climatic data. Most farmers depending on subsistence agriculture have a perception of climate change and respond to the changes based on their own local knowledge and experiences on farming. They are practicing both agricultural and non-agricultural adaptations at individual level. Consequently, appropriate technologies and sustainable community based adaptation strategies built on farmers knowledge, experiences and situation to cope with increasing effects of climate change on agriculture are necessary in the coming years.